Analisis Filsafat terhadap Pentingnya Komunikasi dalam Perilaku Organisasi - Rambe, Ali Akbar; Syahputra, Dermawan; Daulay, Isma Hayati (EduInovasi: Journal of Basic Educational Studies, 2024)
The importance of communication in organizational behavior has significant implications in the context of education. In the educational environment, the aspect of communication is an integral part of the learning process and student development. In education, communication is defined as more than just the exchange of information. From the quote, there is an explanation of the type of research used, namely library research. This research is conducted by accumulating information from various sources, such as books, journals, theses, dissertations, and the internet. Before analyzing the literature, researchers must clearly understand where objective data will be obtained. This research shows that organizational behavior is related to how people act and react in all types of organizations. In organizational life, people are employed, educated and trained, given information, protected, and developed. In other words, organizational behavior is how people behave within an organization.